Inhibition of inflammatory pain and cough by a novel charged sodium channel blocker. (21st June 2021) - Tochitsky, Ivan; Jo, Sooyeon; Andrews, Nick; Kotoda, Masakazu; Doyle, Benjamin; Shim, Jaehoon; Talbot, Sebastien; Roberson, David; Lee, Jinbo; Haste, Louise; Jordan, Stephen M.; Levy, Bruce D.; et al.
Abstract : Background and Purpose: Many pain‐triggering nociceptor neurons express TRPV1 or TRPA1, cation‐selective channels with large pores that enable permeation of QX‐314, a cationic analogue of lidocaine. Co‐application of QX‐314 with TRPV1 or TRPA1 activators can silence nociceptors. In this study, we describe BW‐031, a novel more potent cationic sodium channel inhibitor, and test whether its application alone can inhibit pain associated with tissue inflammation and whether this strategy can also inhibit cough. Experimental Approach: We tested the ability of BW‐031 to inhibit pain in three models of tissue inflammation:‐ inflammation in rat paws produced by complete Freund's adjuvant or by surgical incision and a mouse ultraviolet (UV) burn model. We tested the ability of BW‐031 to inhibit cough induced by inhalation of dilute citric acid in guinea pigs. Key Results: BW‐031 inhibited Nav 1.7 and Nav 1.1 channels with approximately sixfold greater potency than QX‐314 when introduced inside cells. BW‐031 inhibited inflammatory pain in all three models tested, producing more effective and longer‐lasting inhibition of pain than QX‐314 in the mouse UV burn model. BW‐031 was effective in reducing cough counts by 78%–90% when applied intratracheally under isoflurane anaesthesia or by aerosol inhalation in guinea pigs with airway inflammation produced by ovalbumin sensitization. Conclusion and Implications: BW‐031 is a novel cationic sodium channel inhibitor that can be applied locally as a single agent to inhibit inflammatory pain. BW‐031 can also effectively inhibit cough in a guinea pig model of citric acid‐induced cough, suggesting a new clinical approach to treating cough.